Diagnostik und Therapie von Harnröhrenstrikturen – Leitlinienübersicht 2024 : Teil 2 – posteriore Harnröhre - Klemm, Jakob; Dahlem, Roland; Kluth, Luis A; Rosenbaum, Clemens M; Shariat, Shahrokh F; Fisch, Margit; Vetterlein, Malte W; Trauma and Reconstructive Urology Working Party of the European Association of Urology Young Academic Urologists (Urologie (Heidelberg, Germany), 2024)
In light of recently published international guidelines concerning the diagnosis, treatment, and aftercare of urethral strictures and stenoses, the objective of this study was to synthesize an overview of guideline recommendations provided by the American Urological Association (AUA, 2023), the Société Internationale d'Urologie (SIU, 2010), and the European Association of Urology (EAU, 2023). The recommendations offered by these three associations, as well as the guidelines addressing urethral trauma from the EAU, AUA, and the Urological Society of India (USI), were assessed in terms of their guidance on posterior urethral stenosis. On the whole, the recommendations from the various guidelines exhibit considerable alignment. However, SIU and EAU place a stronger emphasis on the role of repeated endoscopic treatment compared to AUA. The preferred approach for managing radiation-induced bulbomembranous stenosis remains a subject of debate. Furthermore, endoscopic treatments enhanced with intralesional therapies may potentially serve as a significant treatment modality for addressing even fully obliterated stenoses.
Keywords: Constriction, Pathologic; Evidence-based medicine; uretra; United States; stenóza; Stenosis; urologie; Pelvic trauma; Humans; endoskopie; striktura uretry; Urethra; Spojené státy americké; Urology; Urethroplasty; lidé; Urethral Stricture; Endoscopy